Transformative Prophetic Leadership as a Strategic Solution for Enhancing Educational Quality - Achmad Qusairi (Journal of Research in Educational Management, 2022)
The transformation of educational institutions in the era of rapid social and technological change has created new challenges for educational leaders, particularly in maintaining quality, institutional values, and sustainable development. Conventional leadership approaches that emphasize administrative functions are increasingly questioned because they often fail to address moral, cultural, and human-centered dimensions of educational management. Therefore, leadership models based on ethical and value-oriented frameworks are becoming an important alternative for strengthening educational quality. This study aims to explore the implementation of prophetic leadership as a transformative approach to improving the quality of education. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis involving the madrasah principal, teachers, and educational staff. Data were analyzed through data reduction, data display, and conclusion verification. The findings reveal that prophetic leadership is implemented through four main dimensions derived from the prophetic mission of Prophet Muhammad SAW, namely humanization, liberation, tolerance and plurality, and moderation. These values are operationalized through the prophetic characteristics of sidiq (integrity), amanah (responsibility), tabligh (effective communication), and fathonah (intellectual competence). The implementation of these principles contributes to strengthening teacher commitment, improving organizational culture, and supporting continuous improvement in educational quality. This study concludes that prophetic leadership provides a transformative leadership framework that integrates ethical values, professional competence, and social responsibility. The study suggests that educational institutions, particularly Islamic schools, should consider prophetic leadership as an alternative model for responding to contemporary leadership challenges and achieving sustainable educational quality improvement.